[The new complexity: new dynamics in clusters and districts] - M Davide Parrilli (European Regional Science Association (ERSA), 2011)
– Recently, service clusters have been identified, such as in the case of the logistics and transportation cluster in the Basque Country (e.g. transportation of people and ware, intelligent transport services, etc.) or that of port activities (warehousing services, loading-unloading of goods, shipping service, etc.). Simultaneously, several multi-sector clusters around a specific client are rising. It is the case of the child cluster in France or in Catalunya that includes much more than traditional clusters focused on a final homogeneous product; in fact this includes the production of toys, kids clothes, health products and furniture for children, among others, which belonged to separate sectors and clusters before. In addition to identifying new types of clusters that strengthen the visibility and work of their firms , the great majority of these clusters and districts, e.g. in the Basque Country, have become more `complex' in depth (division and specialization of labor) and extension to a variety of activities that were quite separated from one another, though can now come together with the objective to respond to the new demand of local and global society. For instance, the demand for new renewable sources of energy promotes a change in sectoral/entrepreneurial attitudes, for which such diversified sectors as oil refinery, wind, maritime and solar energy, find representation in the same cluster association and recognize themselves as part of one 'complex' cluster that gains in visibility and scale of operations for global agents such as large industries, large scale construction projects, among others. The identification and the activity of such clusters and districts, sometimes associated in a specific locality, in other occasions to a wider territory, exhibit the growing awareness of the strengths and diversities of the territorial production fabric and the importance businesses and agents attribute to identifying themselves as such in order to develop joint initiatives that can generate important economies of scale and scope that help competing in the new globalized economy, particularly when these local production systems strive to open their way in global production networks and in international markets.
Keywords: 330